Electrospun free-standing N-doped C@SnO2 anode paper for flexible Li-ion batteries. (January 2019) - Liu, Xing; Jiang, Yunhong; Li, Kefeng; Xu, Fu; Zhang, Ping; Ding, Yanhuai
Graphical abstract: The results from electrochemical testing show that binder-free and self-standing core-shell N-doped C@SnO2 fibers exhibit large initial capacity and excellent flexibility as anode for Li-ion batteries. Highlights: Core-shell N-doped C@SnO2 fibers were prepared from electrospun technique. N-doped C@SnO2 fibers deliver a large initial capacity of 1799 mAhg −1 . N-doped C@SnO2 fabrics exhibit good electrochemical behavior and flexibility. N-doped C@SnO2 fabrics remain high reliability after harsh mechanical operation. Abstract: Electrochemically active SnO2 materials are prospective alternatives for graphite toward better flexible LIBs. However, significant volume changes and structural pulverization restrict the cycling stability and high capacity of SnO2 . Here, we report a binder and conductive additive free core-shell N-doped carbon @SnO2 hybrid paper by a subtle coaxial-electrospinning method. Core-shell N-doped C@SnO2 fibers not only offer rapid ionic transport and sufficient buffer space for the volume expansion during the Li insertion and extraction reactions, but also enable high flexibility against both compression and bending deformation. As an anode for LIBs, the hybrid materials delivered a large initial capacity of 1799 mAhg −1 with capacity retention of 729 mAhg −1 after 100 cycles at a current rate of 390.5 mAg −1 . More importantly, flexible N-doped C@SnO2 fabrics exhibit excellent electrochemical performance even after a rough treatment, suggesting a facile strategy for the fabrication of electrochemically stable electrodes for flexible LIBs.